Trends in cool roof solar reflectivity degradation in New York City (2014–2020): an important consideration for health-based evaluations of high albedo urban roofing interventions - Bonanni, Luke; Bershteyn, Anna; Heris, Mehdi Pourpeikari; Titus, Andrea; Wei, Hanxue; Babayode, Oyinkansola; Rom, William; Azan, Alexander (Frontiers in Sustainable Cities, 2025)
IntroductionGrowing remote sensing and machine learning capabilities offer opportunities to understand the spatiotemporal performance of reflective cool roofs, a widely implemented urban heat mitigation tool, in relation to health. We evaluated cool roof solar reflectivity trends across NYC and in heat-vulnerable communities.MethodsIn this retrospective, longitudinal study, we used satellite-derived cool roof data aggregated to census blocks over 2014–2020. Roofs with a solar reflectivity value ≥ 65 in 2014 were defined as cool roofs with sufficient albedo. Cool roofs with subsequent reflectivity < 65 were considered degraded. We descriptively calculated the cumulative proportion of census blocks that experienced degradation across NYC and in low vs. high heat-vulnerable areas defined by the NYC heat vulnerability index.ResultsOf 18,565 census blocks with at least one building with a cool roof installed and an average cool roof reflectivity ≥ 65 in 2014, 24.56% experienced degradation by 2020. A greater proportion of census blocks experienced degradation by 2020 in low (27.03%) vs. high (21.20%) heat-vulnerable areas. The largest proportion of total, census block-level cool roof degradation occurred between 2014 and 2016 (57.39%).DiscussionWe found strong evidence of cool roof degradation across NYC, which has important implications for future health-based evaluations. Interestingly, a larger proportion of census blocks experienced cool roof degradation in low compared to high-heat vulnerable areas, potentially highlighting the effectiveness of community-led environmental justice initiatives. Municipal maintenance initiatives are needed to ensure the urban heat mitigation potential of cool roofs is sustained.